2014
DOI: 10.1111/aji.12258
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like Receptors at the Maternal‐Fetal Interface in Normal Pregnancy and Pregnancy Complications

Abstract: Toll-like receptors (TLRs) form the major family of pattern recognition receptors (PRRs) that are involved in innate immunity. Innate immune responses against microorganisms at the maternal-fetal interface may have a significant impact on the success of pregnancy, as intrauterine infections have been shown to be strongly associated with certain complications of pregnancy. At the maternal-fetal interface, TLRs are expressed not only in the immune cells but also in non-immune cells such as trophoblasts and decid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 129 publications
0
87
0
1
Order By: Relevance
“…In summary, this is the first study examining TLR1-10 gene expression and activation in a panel of trophoblast cell lines of different origins. Trophoblast TLR activation has been implicated in pregnancy outcome and fetal development [13], but more research is needed to elucidate the consequence of placental TLR activation in normal and pathologic pregnancies. The use of trophoblast cell lines is crucial in achieving these goals.…”
Section: Multivariate Analysis Of Tlr Gene Expression and Cytokine Rementioning
confidence: 99%
See 1 more Smart Citation
“…In summary, this is the first study examining TLR1-10 gene expression and activation in a panel of trophoblast cell lines of different origins. Trophoblast TLR activation has been implicated in pregnancy outcome and fetal development [13], but more research is needed to elucidate the consequence of placental TLR activation in normal and pathologic pregnancies. The use of trophoblast cell lines is crucial in achieving these goals.…”
Section: Multivariate Analysis Of Tlr Gene Expression and Cytokine Rementioning
confidence: 99%
“…Ten different human TLRs, each responding to a specific set of ligands, have been identified [4]. TLR expression and activation in primary trophoblasts [5][6][7][8][9][10] may contribute substantially to development of inflammatory pregnancy complications such as preeclampsia [11][12][13]. In Tangerås/Stødle et al [7] we demonstrated a broad functional TLR profile in primary first trimester trophoblasts, while the trophoblast cell line BeWo showed no TLR mediated cytokine response.…”
Section: Introductionmentioning
confidence: 95%
“…Toll-like receptors (TLRs) are a family of newly discovered receptors that are crucial for innate immunity and are highly conserved in all invertebrates and vertebrates (Pevsner-Fischer et al, 2007). It has been reported that TLRs are involved in the maintenance of pregnancy and occurrence of pregnancy disorders (Amirchaghmaghi et al, 2013;Koga et al, 2014). Both amnion cells and trophocytes at the maternal-fetal interface may be involved in innate immunity by the activation of TLRs, which then affects the outcome of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Among eleven different TLRs identified in humans, the trans-membrane TLR2 and TLR4, the most studied ones, are the first line of immune defense against bacteria, viruses, fungi and parasites [24]. Expressed both in the periphery and in the central nervous system (CNS) as well as in the maternal-fetal interface, they are able to initiate immediate immune responses against invading pathogens with potential implications in neuropathological processes [25][26][27]. This is of particular relevance since a variety of infectious agents viz Borna virus, Toxoplasma gondii, influenza or herpes simplex I have been associated with BD [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%